Downregulation of miR-27b is Involved in Loss of Type II Collagen by Directly Targeting Matrix Metalloproteinase 13 (MMP13) in Human Intervertebral Disc Degeneration. Issue 3 (February 2016) - Li, Hao-ran; Cui, Qing; Dong, Zhan-yin; Zhang, Jian-hua; Li, Hai-qing; Zhao, Ling
Abstract : Study Design: A microRNA (miRNA) study. Objective: The purpose of this study was to identify intervertebral disc degeneration (IDD)-specific miRNAs, followed by functional validation of results. Summary of Background Data: IDD is the major contributor to back radicular pain, and the molecular mechanisms underlying this disease are not completely understood. Accumulating evidence suggests that miRNAs play an important role in IDD, but the role of specific miRNAs involved in this disease remains elusive. Methods: An initial screening of nucleus pulposus (NP) tissues, miRNA expression by miRNA microarray, was performed using samples from 10 patients with degenerative disc disease and 10 patients with lumbar fracture (as controls). Subsequently, differential expression was validated using quantitative reverse transcriptase PCR (qRT-PCR). The level of differentially expressed miRNAs in degenerative NP tissues was investigated, and then functional analysis of the miRNAs in regulating collagen II expression was carried out. Western blotting and luciferase reporter assays were also used to detect the target gene. Results: We identified 23 miRNAs that were differentially expressed (16 upregulated and 7 downregulated) in patients compared with controls. After qRT-PCR confirmation, miR-27b was significantly downregulated in degenerative NP tissues when compared with controls. Moreover, its level was correlated with grade of disc degeneration. Overexpression of miR-27b promoted type II collagen expression in NP cells. Bioinformatics target prediction identified matrix metalloproteinase 13 (MMP13) as a putative target of miR-27b. Futhermore, luciferase reporter assays demonstrated that miR-27b directly targets MMP13 and affects the protein expression of MMP13 in NP cells. Expression of MMP13 negatively correlated with miR-27b expression in degenerative NP tissues. Conclusion: The downregulation of miR-27b induces type II collagen loss by directly targeting MMP13, leading to the development of IDD. Our study also underscores the potential of miR-27b as a novel therapeutic target in human IDD. Level of Evidence: 3